Implementation of sustainable innovation as sharia-based on the resto-pool development strategy of business - Dina Nur Wulandari; Muhammad Ahsan (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Thesis with the title